Shear damage constitutive model of rock-like joint surface considering the coupling effect of cyclic water intrusion and loading - Qin, Zhe; Zhang, Runchang; Wang, Ke; Cao, Lixue; Yan, Yushui (International journal of mining science and technology, 2025)
Prolonged cyclic water intrusion has progressively developed joints in the hydro-fluctuation belt, elevating the instability risk of reservoir bank slopes. To investigate its impact on joint shear damage evolution, joint samples were prepared using three representative roughness curves and subjected to direct shear testing following cyclic water intrusion. A shear damage constitutive model considering the coupling effect of cyclic water intrusion and load was developed based on macroscopic phenomenological damage mechanics and micro-statistical theory. Results indicate: (1) All critical shear mechanical parameters (including peak shear strength, shear stiffness, basic friction angle, and joint compressive strength) exhibit progressive deterioration with increasing water intrusion cycles; (2) Model validation through experimental curve comparisons confirms its reliability. The model demonstrates that intensified water intrusion cycles reduce key mechanical indices, inducing a brittle-to-ductile transition in joint surface deformation — a behavior consistent with experimental observations; (3) Damage under cyclic water intrusion and load coupling follows an S-shaped trend, divided into stabilization (water-dominated stage), development (load-dominated stage), and completion stages. The research provides valuable insights for stability studies, such as similar model experiments for reservoir bank slopes and other water-related projects.